Analisis Risiko Produksi Olahan Kopi Arabika Pada Kopi Langit Bali di Desa Catur, Kecamatan Kintamani, Kabupaten Bangli: Analisis Risiko Produksi Olahan Kopi Arabika Pada Kopi Langit Bali di Desa Catur, Kecamatan Kintamani, Kabupaten Bangli - Indraswari, Kadek Renita; Dewi, Ni Luh Prima Kemala (Journal Science Innovation and Technology (SINTECH), 2025)
Kopi Langit Bali is a UMKM that produces processed Arabica coffee, including green beans, roasted beans, and ground coffee, using natural, honey, and full washed methods. During the production process, Kopi Langit Bali often faces challenges filled with uncertainty and needs to be wary of the potential risks in its production activities, thus requiring an early risk analysis to ensure business sustainability. This research aims to identify potential risks during the production process, analyze the severity, frequency, and detection capability of risks using the Failure Mode and Effects Analysis (FMEA) method, and formulate mitigation strategies to reduce potential risks. The research was conducted on the production process of Kopi Langit Bali in 2024. The research results show that there are 13 risk events and 13 risk agents in the production process. The highest risk in the Intolerable (INT) category has an RPN value of 775, and the lowest risk is in the Broadly Acceptable (BA) category with an RPN of 6. Two risk agents were identified as mitigation priorities because they fall into the INT and ALARP categories. Based on the analysis results, three main mitigation strategies have been formulated that can be applied by Kopi Langit Bali, including (1) implementing coffee planting patterns with shade to mitigate the impact of extreme weather, (2) maximizing drying capacity within the greenhouse, and (3) building affective commitment with freelance workers.